Effects of low-dose aspirin on clinical outcome and disease progression in patients with gastroenteropancreatic neuroendocrine neoplasm. (2nd September 2019) - Cavalcoli, Federica; Pusceddu, Sara; Zilli, Alessandra; Tamagno, Gianluca; Femia, Daniela; Prinzi, Natalie; Travers, John; Consonni, Dario; Ciafardini, Clorinda; Conte, Dario; Massironi, Sara
Abstract: Objective: The chemopreventive effect of aspirin (ASA) has been observed in the setting of colorectal cancer and other solid neoplasms. Recently, ASA has demonstrated a promising anti-proliferative effect on GEP-NENs in vitro . However, the direct anti-neoplastic impact of ASA on GEP-NEN clinical outcome is yet to be clarified. Materials and methods: All the GEP-NEN patients followed up in three European Centers from January 2005 to September 2016 were retrospectively enrolled. Patients taking ASA in doses of 75–100 mg daily for cardiovascular prevention for at least six months were evaluated. The possible association between ASA and disease grading, staging, primary site, OS and PFS were evaluated. Results: Two hundred fifty one patients were included (117 males, median age 63 years). Of these, 64 patients were prescribed with ASA. No clear impact on OS or PFS was observed in GEP-NEN patients taking ASA compared to those not taking it. ASA intake was related with the patients' older age. At Cox multivariate analysis, stage IV and Ki-67 resulted independent predictors for OS and PFS. In the setting of intestinal NENs, a suggestive, but not statistically significant, protective role of ASA on PFS was observed [HR 0.41 (95% CI: 0.13–1.29)]. Conclusions: Despite ASA showed promising anti-proliferative effects in vitro and a chemopreventive action in NENs has been reported, a clear impact of ASA on survival in NENs has not emerged from the present study. However, in the subgroup of patients with small-intestine NENs, ASA showed a trend toward a protective role.